PROTECTION OF PERSONAL DATA - DIMENSION OF THE RIGHT TO PRIVATE LIFE. FUNDAMENTAL REGULATIONS - Oana ŞARAMET (US ET CIVITAS, Vol. V (LXIX), 2018)
Since the proclamation of the fundamental rights of every human being through the Universal Declaration of Human Rights, by the pacts, protocols, charts, conventions, declarations that have followed it at international or regional level, often even through their preamble, a "Given" to any of us, regardless of nationality, citizenship, age, gender, color, social or ethnic origin, race, language, religion, opinion, political affiliation, wealth, namely human dignity. Recognizing this quality of any human being, implicitly, in our opinion, it was necessary, at least recognized, if not even protected and even guaranteed, the existence of a private life and, implicitly, a right to it. The content and dimensions of this right have not been established in international documents, and it is preferable that their identification be made through the institutions or courts, where appropriate, responsible for guaranteeing recognition and enforcement of this right. Thus, it was possible to continually and continuously update this content by reference to the social reality in a continuous evolution. So we can now see what is meant by the concept of private life today, but that we can no longer ignore one of its dimensions, which should be acknowledged not only by a legal consecration, but also by an effective application of legal provisions, namely the protection of personal data precisely in order not to affect the private life of a human being, nor, implicitly, its dignity.
Keywords: human dignity; law; privacy; protection; personal data